ANALISIS KETERLAKSANAAN MODEL PROBLEM BASED LEARNING (PBL) DAN PENGARUHNYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DI SMA - Buyung Buyung (PHI: Jurnal Pendidikan Matematika, 2017)
This study aims to determine the implementation of the problem-based learning model and its effect on the ability of solving mathematical problems in high school. The research method uses a quantitative approach. Mathematical troubleshooting capability data using essay test and problem-based learning disabilities using observation sheets of teacher and student activities. sample taken by random sampling technique amounted to 38 students. The test of the implementation of problem-based learning model is tested by two-sided equation with -ttable < thitung< ttableresult that is -2,44 <0,22 <2,44 this means that the implementation of PBL model on activity by student can represent activity model activity by teacher. to see the effect of using the t test, the results show thitung>ttableie 3.247> 2.03 means there is influence implementation of problem-based learning model of students' mathematical problem solving abilities.Keywords:     Analysis, problem based learning model, problem solving ability mathematically